Power Control in a Hybrid Isolated Power System with Better Power Quality - B. Mouli Chandra, B. Venkata Prasanth, Ahmad Syed, Prakash Y. (Mathematical Statistician and Engineering Applications, 2023)
Hybrid power systems are the combination of different renewable energy conversion systems like solar energy, fuel cell, wind energy, tidal energy, geothermal energy etc,. They are considered as a reliable and viable option for the electrification of rural villages which are beyond the reach of proper grid electricity. The control of power among different renewable sources while maintaining the power quality of supply is important for the reliable and sustainable operation of these isolated systems. This idea proposes a flexible and versatile solution to voltage quality problems is offered by active power filters APF. Where the reactive power, harmonics and unbalance in the load power are always supplied by one photovoltaic inverter, while the active power is shared by another photovoltaic inverter and fuel cell based on the load requirement. This power sharing control increases the power reliability and power quality of isolated village hybrid power systems. The detailed simulation is studied in MATLAB SIMULINK